PENGARUH KUALITAS PELAYANAN, CITRA MEREK, DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN JASA TRANSPORTASI GOCAR DI KOTA BATAM - Roland Marudut Leonardo,; Riki, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
This study aims to determine: The effect of service, brand image and price perceptions on customer satisfaction of the users transport service online Gocar in Batam City. This research is a survey research used purposive sampling with the number of samples counted 200 respondents. There is the positive influence of service proved by tvalue 7.368 > ttables 1.652, and Significance value 0,000<0.05, brand image proved by tvalue 4.994 > ttables 1.652 and significance value 0,000 <0.05, price perception, proved by tvalue 3.774 > ttables 1.652; Significance value 0,000<0.05, on customer satisfaction of the users transport service online Gocar in Batam City and there is influence of service quality, price perception, and brand image together on customer satisfaction of the users transport service online Gocar in Batam City, evidenced by Fvalue count equal to 129.422 > Ftables2.65 and significance 0,000 <0,05.